Neuronal symphonies: Musical improvisation and the centrencephalic space of functional integration. Issue 8 (17th November 2017) - Maldonato, Mauro; Oliverio, Alberto; Esposito, Anna
Abstract : Musical improvisation is a sophisticated activity in which a performer realizes, real-time, melodic, and rhythmic sequences in harmony with those from other musicians. The study of musical improvisation helps one to understand not only the cognition of creativity, but also the complex neuronal basis of executive functions, the relation between conscious and unconscious action, and even more. So far, the prevailing models, founded on the brain imaging method, have focused on the connection between the cortical areas and their cognitive processes. Little attention, on the other hand, has been given to the huge variety of subcortical activities, especially in the basal ganglia. This fundamental subcortical component, through its implicit procedures and the role it plays in memory, is responsible to produce new information all the time, allowing the prefrontal cortex to transform a huge and disordered amount of data in explicit creative acts. The basal ganglia are strongly related to the activation of chemical signals generated by dissonance or lack of symmetry between perception and expectation, participating even in the responses to environmental demands according to the circumstances. Thus, they interact with the frontal cortex and with the limbic system, playing a key role in planning and selecting appropriate actions and in decision making. In this text, we try to explain in which sense improvisation is connected to the processes of executive functions, to creativity and to the integrated activity of cortical–subcortical areas controlling the free flow of ideas and to expressive spontaneity. Eventually, we purpose a model according to which structure (improvisational field) and process (improvisational time) take part at the centrencephalic space of functional integration, which, through both competing and cooperating dynamics, gives way to spontaneous composition.